Gneyulins A and B, stilbene trimers, and noidesols A and B, dihydrofluvonol-C-Glucosides, from the Bark of gnetum gnemonoides - Shimokawa, Y.; Akao, Y.; Hirasawa, Y.; Awang, Khalijah; Hadi, A.H.A.; Sato, S.; Aoyama, C.; Takeo, Ji.; Shiro, M.; Morita, H. (American Chemical Society, 2010)
Gneyulins A (1) and B (2), two new stilbene trimers consisting of oxyresveratrol constituent units, and noidesols A (3) and B (4), two new dihydroflavonol-C-glucosides, were isolated from the bark of Gnetum gnemonoides. The structures and configurations of 1-4 were elucidated on the basis of 2D NMR correlations and X-ray analysis. Gneyulins A (1) and B (2) showed inhibition of Na(+) glucose transporters (SGLT-1 and SGLT-2).